Anisotropic physical properties of PrRhAl4Si2 single crystal: A non-magnetic singlet ground state compound. (August 2016) - Maurya, Arvind; Kulkarni, R.; Thamizhavel, A.; Dhar, S.K.
Abstract: We have grown the single crystal of PrRhAl4 Si2, which crystallizes in the tetragonal crystal structure. From the low temperature physical property measurements like, magnetic susceptibility, magnetization, heat capacity and electrical resistivity, we found that this compound does not show any magnetic ordering down to 70 mK. Our crystal field calculations on the magnetic susceptibility and specific heat measurements reveal that the 9-fold degenerate ( 2 J + 1 ) levels of Pr atom in PrRhAl4 Si2 split into 7 levels, with a singlet ground state and a well-separated excited doublet state at 123 K, with a overall level splitting energy of 320 K. Abstract : Highlights: Single crystals of PrRhAl4 Si2 have been grown using Al:Si eutectic composition as flux. Laue diffraction pattern confirmed the good quality of the single crystal. Anisotorpic physical properties of PrRhAl4 Si2 were investigated. PrRhAl4 Si2 exhibits a non-magnetic singlet ground state. Crystal electric field analysis reveals that the 9-fold degenerate (2 J +1) levels of Pr atoms split into 7 levels.